To be or not to be like Iceland?:(Ontological) Politics of comparison in Greenlandic tourism development - Ren, Carina; Jóhannesson, Gunnar Thór (Polar Record, 2023)
In this article, we introduce the concept of ‘politics of comparison’ in tourism development, looking at how comparison contributes to shaping and making sense of tourism development in Greenland. Decision makers and operators in Greenland foresee tourism growth as new transatlantic airports are set to open by 2024. To navigate an uncertain tourism future, many look towards neighbouring Iceland, who experienced exponential growth in international tourism arrivals between 2010 and 2018. In this North Atlantic reflection, comparison also works as a tool to understand tourism, positioning Greenland as a potential destination and deliberating about the future of tourism in the region, while also bringing forth competing logics and trajectories of development. Thus, comparison serves to engage with the meaning and value of tourism, seeing it not only as a pillar of the economy but also as a force affecting landscapes and communities. We argue that the comparisons made by tourism actors work epistemologically - creating knowledge of ‘what is’ - as well as ontologically, forcefully interfering with and producing tourism realities.